TERMINAL BUILDING WITH ECO-FUTURISTIC DESIGN IN TRANSIT ORIENTED DEVELOPMENT (TOD) MEDAN LABUHAN - Inayah Oktalia; Suwantoro, Hajar (Talenta Publisher, 2022)
Based on the 2006-2031 RUTR Medan which will develop a Transit Oriented Development (TOD) in Medan Labuhan, it becomes the background of this student final project. This project aims to design a hub consists of terminal building, commercial, office building and some other public functions focusing on mobility of workers in Kawasan Industri Medan (Medan industrial area) in Medan Labuhan. The terminal building accommodates several transportation modes such as local buses, MRT and inter-regional buses. This project applies the principles of eco-futuristic architecture to gain some futuristic form to indicates the future of Medan.